Statistical analysis for the oscillation frequency of a ring oscillator - Wanjing Zhu; Tan Lu; Weijie Zhu; Jianguo Ma (2010 IEEE International Conference of Electron Devices and Solid-State Circuits, 2010)
It is important to find the statistical characteristics of the ring oscillators in mass production but the computational complexity prevents us from finding the distribution of these characteristics. Consequently, predicting the statistical parameters of these characteristics is much more practical. This paper derives the mathematical relationship between the variation of the capacitances and the process variations. And the Monte Carlo Method is used to build three linear prediction equations for the variation of oscillation frequency.